Coping with pandemics using social network sites: A psychological detachment perspective to COVID-19 stressors - Mäntymäki Matti; Najmul Islam AKM; Turel Ofir; Dhir Amandeep (Elsevier, 2025)
Prior research has often portrayed information technology (IT) as a stressor. In this paper, we propose and demonstrate that IT can also be an effective means of coping with life stressors, including those induced by pandemics such as COVID-19. We thus deviate from the common IT-as-a-stressor perspective and adopt an IT-as-a-coping-mechanism viewpoint. To this end, we apply the stressor-detachment model from organisational psychology to the use of social network sites (SNSs) in coping with stressors wrought by the COVID-19 pandemic. We examine psychological well-being as our dependant variable and introduce psychological detachment through SNS use as a mediator and moderator of the associations between psychological well-being and two COVID-19 stressors: work-family conflict and perceived isolation. We used structural equation modelling and tested this model with survey data collected from 398 professionals who were in lockdown and working from home during the pandemic. The results indicated that psychological detachment through SNS uses increased psychological well-being and that heightened work-family conflict motivated this detachment strategy. In contrast, consistent with helplessness and motivation-opportunity theories, perceived isolation as a stressor did not influence psychological detachment through SNS use. While perceived isolation directly reduced individual well-being, the effect of work-family conflict on well-being was contingent upon users' levels of psychological detachment through SNS use. These findings suggest that while psychological detachment through SNS use is an effective means of improving one's well-being, it can be positively or negatively affected by stressors. Our study contributes to research on technology-mediated strategies for coping with stress and the psychosocial implications of global pandemics.